Thermodynamic entropy generation in the course of the fatigue crack initiation. Issue 3 (2nd August 2016) - Ontiveros, V; Amiri, M; Kahirdeh, A; Modarres, M
Abstract: Evolution of the thermodynamic entropy generation during fatigue crack initiation life of notched specimens is studied. A set of experimental results of AA7075‐T651 is examined to determine applicability of the thermodynamic entropy generation as an index of fatigue crack initiation. Entropy accumulation is calculated from hysteresis energy and temperature rise. An increasing trend of entropy accumulation with the number of cycle to failure is observed on macroscale measurements. Results also determine that the entropy generations from the samples under the same operating conditions are similar as the crack grows. Scanning electron microscope analysis is performed on the fractured surfaces to observe the fatigue striations, and persistent slip bands are observed employing an optical microscope. A discussion is presented regarding the length scales on which crack initiation occurs and entropy calculation is made.